Intratumoral Mistletoe (Viscum album L) Therapy in Patients With Unresectable Pancreas Carcinoma: A Retrospective Analysis. (July 2014) - Schad, Friedemann; Atxner, Jan; Buchwald, Dirk; Happe, Antje; Popp, Stephan; Kröz, Matthias; Matthes, Harald
Pancreatic carcinoma remains one of the main causes for cancer-related death. Intratumoral application of anticancer agents is discussed as a promising method for solid tumors such as pancreatic cancer. Endoscopic ultrasound provides a good tool to examine and treat the pancreas. European mistletoe ( Viscum album L) is a phytotherapeutic commonly used in integrative oncology in Central Europe. Its complementary use seeks to induce immunostimulation and antitumoral effects as well as alleviate chemotherapeutic side effects. Intratumoral mistletoe application has induced local tumor response in various cancer entities. This off-label use needs to be validated carefully in terms of safety and benefits. Here we report on 39 patients with advanced, inoperable pancreatic cancer, who received in total 223 intratumoral applications of mistletoe, endoscopic ultrasound guided or under transabdominal ultrasound control. No severe procedure-related events were reported. Adverse drug reactions were mainly increased body temperature or fever in 14% and 11% of the applications, respectively. Other adverse drug reactions, such as pain or nausea, occurred in less than 7% of the procedures. No severe adverse drug reaction was recorded. Patients received standard first- and second-line chemotherapy and underwent adequate palliative surgical interventions as well as additive subcutaneous and partly intravenous mistletoe application. A median survival of 11 months was observed for all patients, or 11.8 and 8.3 months for stages III and IV, respectively. Due to the multimodal therapeutic setting and the lack of a control group, the effect of intratumoral mistletoe administration alone remains unclear. This retrospective analysis suggests that intratumoral-applicated mistletoe might contribute to improve survival of patients with pancreatic cancer. In conclusion, the application is feasible and safe, and its efficacy should be evaluated in a randomized controlled trial.